From Tradition to Transformation: A Scientific Blueprint for Safer Tofu in Bandar Lampung - Subara, Deni; Kumala, Reza; Sylvia, Teny (UNIVERSITAS MUHAMMADIYAH MATARAM, 2025)
Tofu is an affordable, ubiquitous protein source, but its production, especially in small and medium-sized enterprises (SMEs) using traditional methods, presents significant microbiological risks. To address these risks, we analyzed the production process of a local producer,